2022
DOI: 10.1021/acs.macromol.1c02252
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Free-Radical/Cationic Phase-Separated UV-Curable System: Impact of Photoinitiator Content and Monomer Fraction on Surface Morphologies and Gloss Appearance

Abstract: Simultaneous photopolymerization of radical and cationic systems is one strategy to generate polymer network architectures named interpenetrating polymer networks (IPNs). In these hybrid systems, phase separation and final polymer morphology are ultimately governed by thermodynamic incompatibility and polymerization kinetics. This behavior is quite complex, as numerous factors can affect polymerization kinetics including monomer/oligomer viscosity and structure, light intensity, photoinitiator content and abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In our previous study [35], we demonstrated the immiscibility of CE and PBDUA prior to photopolymerization, which was dependent on the ratio of these two species. Based on these findings, a third monomer was included (HDDMA) in the mixtures studied here, to ensure compatibility.…”
Section: Determination Of the Phase Diagram For The Ternary Mixture A...mentioning
confidence: 80%
See 3 more Smart Citations
“…In our previous study [35], we demonstrated the immiscibility of CE and PBDUA prior to photopolymerization, which was dependent on the ratio of these two species. Based on these findings, a third monomer was included (HDDMA) in the mixtures studied here, to ensure compatibility.…”
Section: Determination Of the Phase Diagram For The Ternary Mixture A...mentioning
confidence: 80%
“…Specifically, thermodynamics dictates the degree of incompatibility between monomers and monomer-polymer solutions and, thus, the driving force for phase segregation. According to our previous study, CE and PBUDA show incompatibility in their monomer liquid states, depending on their ratio, which leads to the formation of a heterogeneous and totally phase-separated network [35].…”
Section: Miscibility Studies Of a Ternary Free-radical/cationic Mixturementioning
confidence: 91%
See 2 more Smart Citations
“…As the reaction progresses, the viscosity of the solution increases, and radicals can become occluded in the growing polymer network. This radical trapping is a prevalent termination step for glassy photopolymers such as Bis-EMA, which can become vitrified before all monomer is consumed [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%